Signaling network inhibition by selected traditional Chinese medicine preparations: a novel multi-target paradigm for colorectal cancer therapy - Zhang, Mingming; Wang, Haoyang; Pan, Junying; Jin, Yuzhe; Tan, Zengde (Frontiers in Pharmacology, 2026)
Colorectal cancer (CRC) remains a significant global health burden, with drug resistance, recurrence, and metastasis posing major therapeutic challenges. Traditional Chinese Medicine (TCM), employing a holistic “multi-component, multi-target, multi-pathway” strategy, offers a promising complementary approach. This review systematically summarizes recent advances in how TCM monomers and formulations regulate key CRC signaling pathways—including PI3K/Akt/mTOR, MAPK, Wnt/β-catenin, Hedgehog, and NF-κB—to inhibit tumor proliferation, promote apoptosis, suppress metastasis, and remodel the tumor microenvironment. Emphasis is placed on TCM’s unique modulation of pathway crosstalk, providing new insights into its ability to reverse drug resistance and enhance chemosensitivity. The review further proposes and discusses the future translational potential of TCM-based “signaling network inhibitors” as an innovative strategy in CRC management.